PENDEKATAN KRITIK NARATIF A.H. JOHNS TERHADAP NARASI DIALOG DALAM SURAH YUSUF - Akrimi - Matswah (SUHUF, 2018)
The (narrative?) verses in the Qur'an do not only occupy a dominant position, but also demonstrate the Qur'an's literary dimension. Consequently, the narrative criticical approach when studying Qur'anic stories becomes very important, especially in discovering their literary elements and the meanings they contain. This approach, as applied by A.H. Johns in studying the story of Joseph, focused on the dialogues found within the structure of the story. Johns found that the series of dialogues in the story of Joseph that use unusual phrases and idioms not only form a dramatic structure in the presentation of the story but also give clues to the meaning that the Qur'an would reveal. Thus, Johns' study made a significant contribution to the literary discourse of the Qur'an. Keywords Joseph story, narrative criticism, dialogue.